Large Mesh Deformation Using the Volumetric Graph Laplacian - Zhou, Kun; Huang, Jin; Snyder, John; Liu, Xinguo; Bao, Hujun; Guo, Baining; Shum, Heung-Yeung (Association for Computing Machinery, Inc., 2005)
We present a novel technique for large deformations on 3D meshes using the volumetric graph Laplacian. We first construct a graph representing the volume inside the input mesh. The graph need not form a solid meshing of the input mesh’s interior; its edges simply connect nearby points in the volume. This graph’s Laplacian encodes volumetric details as the difference between each point in the graph and the average of its neighbors. Preserving these volumetric details during deformation imposes a volumetric constraint that prevents unnatural changes in volume. We also include in the graph points a short distance outside the mesh to avoid local self-intersections. Volumetric detail preservation is represented by a quadric energy function. Minimizing it preserves details in a least-squares sense, distributing error uniformly over the whole deformed mesh. It can also be combined with conventional constraints involving surface positions, details or smoothness, and efficiently minimized by solving a sparse linear system. We apply this technique in a 2D curve-based deformation system allowing novice users to create pleasing deformations with little effort. A novel application of this system is to apply nonrigid and exaggerated deformations of 2D cartoon characters to 3D meshes. We demonstrate our system’s potential with several examples. https://youtu.be/mcY0J4i2TJ8https://youtu.be/6sibK_QlSmk https://youtu.be/_AoC6JYxKVo https://youtu.be/gipMd8Tfffg https://youtu.be/GT-JIzE1fZw https://youtu.be/ul-pbilJkAg https://youtu.be/sod_o1DgjoI https://youtu.be/eRjIdAYgsQQ https://youtu.be/OQucSf-TgJk https://youtu.be/P5DtHVflwhY